2021
DOI: 10.1038/s41467-020-20553-x
|View full text |Cite|
|
Sign up to set email alerts
|

Functional cooperativity between the trigger factor chaperone and the ClpXP proteolytic complex

Abstract: A functional association is uncovered between the ribosome-associated trigger factor (TF) chaperone and the ClpXP degradation complex. Bioinformatic analyses demonstrate conservation of the close proximity of tig, the gene coding for TF, and genes coding for ClpXP, suggesting a functional interaction. The effect of TF on ClpXP-dependent degradation varies based on the nature of substrate. While degradation of some substrates are slowed down or are unaffected by TF, surprisingly, TF increases the degradation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Thus, the data suggest that bacterial Hsp90 is involved in the sorting of aggregation-prone proteins toward native refolding by the Hsp70/Hsp40 system, or in case of Hsp70/Hsp40 failure, toward more degradation, for example through the HslUV protease. Such interplay between chaperones and proteases has been observed in E. coli, where trigger factor (TF) specifically cooperates with the ClpXP protease to promote the degradation of specific proteins, which represent a significant portion (about 2%) of newly synthesized proteins (Rizzolo et al, 2021). Accordingly, it has been demonstrated that in the α-proteobacterium Caulobacter crescentus, DnaK depletion is suppressed by HslUV, by attenuating the activity of the σ 32 factor (Schramm et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the data suggest that bacterial Hsp90 is involved in the sorting of aggregation-prone proteins toward native refolding by the Hsp70/Hsp40 system, or in case of Hsp70/Hsp40 failure, toward more degradation, for example through the HslUV protease. Such interplay between chaperones and proteases has been observed in E. coli, where trigger factor (TF) specifically cooperates with the ClpXP protease to promote the degradation of specific proteins, which represent a significant portion (about 2%) of newly synthesized proteins (Rizzolo et al, 2021). Accordingly, it has been demonstrated that in the α-proteobacterium Caulobacter crescentus, DnaK depletion is suppressed by HslUV, by attenuating the activity of the σ 32 factor (Schramm et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Degradation observed in the ΔsspB strain was similar to that observed for WT and ΔclpX strains, corroborating the redundancy of the ClpX pathway or the SspB itself. Recently, it was shown that the E. coli ribosome-associated trigger factor (TF), a chaperonin which is highly abundant in the cell and acts early during the folding process, enhances degradation in vitro and in vivo of various ClpXP complex substrates including ssrA-taged proteins (Rizzolo et al , 2021). The role of TF as an additional adaptor could contribute to the lack of an effect of sspB deletion on our tested eGFP-degrons.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, elaborate feedback loops exist, in which either adaptors are themselves recognized as Clp protease substrates or Clp-ATPases, in a ClpP-independent chaperone function, protect substrates from Clp protease degradation ( Kirstein et al, 2009b ). Recently, it was also detected that the ribosome-associated trigger factor chaperone Tig modulates substrate degradation rates of ClpXP ( Rizzolo et al, 2021 ).…”
Section: Physiological Functions and Operation Mode Of The Clp Protease In Various Organismsmentioning
confidence: 99%
“…In Leptospira , trigger factor (TF) is chromosomally colocalized with ClpP and ClpX, and the same applies to E. coli and many other organisms. This observation led two research teams to test a potential functional connection ( Choudhury et al, 2021 ; Rizzolo et al, 2021 ). The addition of TF to Leptospira ClpXP stimulated casein degradation by the protease ( Choudhury et al, 2021 ).…”
Section: Dysregulation Of the Bacterial Clp Protease By Acyldepsipeptide Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation